Implementasi program pendidikan lingkungan hidup dalam proyek penguatan profil pelajar Pancasila di sekolah dasar - Diva Izma Afia; Septi Yulisetiani (Universitas Sebelas Maret, 2025)
This study aims to (1) Describe the implementation of environmental education programs in the Pancasila student profile strengthening project at elementary school, and (2) Describe supporting factors and inhibiting factors for the implementation of environmental education programs in the Pancasila student profile strengthening project at elementary school. This type of research is a qualitative case study. Data collection techniques use interviews, observations, and questionnaires. The data analysis technique uses Cresswell data analysis. The results of the study found that the environmental education program in the Pancasila student profile strengthening project at elementary school was successfully implemented with reference to the assessment indicators, namely using an environmental-based curriculum, having an environmentally-based school culture, and having facilities and infrastructure that support the program. The implementation of the environmental education program in the Pancasila student profile strengthening project has supporting factors, namely: (1) The school has partners who support the program, (2) The school is an Adiwiyata school, (3) The school has adequate environmental facilities and infrastructure, (4) The school has competent teaching staff, and (5) The school has environmental conditions that support the creation of optimal environmental learning, while the inhibiting factors include: (1) Limited aspiration funds for improving facilities and infrastructure, and (2) Several school residents who are not yet consistent in responding to the environment properly.